TourSpot - Lopes, Miguel (2019)
The fast growth in the use of smartphones and the development of new applications are a new and different way of travel and to discover new maps as well as social interaction. In this respect, we saw the need of developing an online tourism application in which it allows our customers to use our application as a guide in order to provide services or as customers to use our services. The aim is to simplify and improve the tourist experience of an individual by conducting city tours of the tourist’s destination, with the support of people from different cultures as well as easing mobility and the knowledge of the city’s gastronomy experience using a single application.